Answer:
f(x) = (x -3)^2 - 1
Step-by-step explanation:
f(x) = x^2 - 6x + 8
a = 1, b = -6 and c = 8
So we are finding half of the b equation (ignore the negative sign)
Half of 6 is 3, so we are going to square 3 (3^2 = 9) and add 9 to the left side and subtract 9 to the right side
(x) = (x^2 - 6x + 9) + (8 - 9)
You can tell the polynomial is a perfect square, so we will have to factor it using the perfect square method
(x^2 - 6x + 9)
square toot of x^2 is x and square root of 9 is 3 and the operation sign after the a number is a minus sign
(x -3)^2
Don't forget the rest of the equation from before
(x -3)^2 + (8 - 9)
(x -3)^2 - 1
So the equation is f(x) = (x -3)^2 - 1
The answer is a because I wired it out
<span>how many services you had if you were charged $115?
set f(x) to 115 and solve for x:
f(x) = 15x + 25
115 = 15x + 25
90 = 15x
6 = x</span>
isosceles triangle has its 2 side equals and thus 2 angles opposite to equal side are equal.
consider in a triangle ABC
AB = AC then Angle B = Angle C
so here given angle B = 36
so angle C = 36
now in a triangle sum of all 3 angles is 180
so
angle A + angle B +angle C = 180
angle A + 36 +36 = 180
angle A = 180 - 72 = 108
2)
in a right angle triangle one angle is 90. another one is given as 28
so we kNow sum of all 3 angles is 180
so
third angle + 90 + 28 = 180
third angle = 180 - 118 = 62